A community for students.

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

anonymous

  • one year ago

y = 3x + 3 y = x − 1 Explain how you will solve the pair of equations by substitution. Show all the steps and write the solution in (x, y) form.

  • This Question is Closed
  1. TheSmartOne
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Any ideas?

  2. TheSmartOne
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Do you know what the substitution method is?

  3. TheSmartOne
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    and not to forget... \(\bf\huge~~~~\color{#ff0000}{W}\color{#ff2000}{e}\color{#ff4000}{l}\color{#ff5f00}{c}\color{#ff7f00}{o}\color{#ffaa00}{m}\color{#ffd400}{e}~\color{#bfff00}{t}\color{#80ff00}{o}~\color{#00ff00}{O}\color{#00ff40}{p}\color{#00ff80}{e}\color{#00ffbf}{n}\color{#00ffff}{S}\color{#00aaff}{t}\color{#0055ff}{u}\color{#0000ff}{d}\color{#2300ff}{y}\color{#4600ff}{!}\color{#6800ff}{!}\color{#8b00ff}{!}\\\bf ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~Made~by~TheSmartOne\) Hey there!!! Since you are new here, read this legendary tutorial for new OpenStudiers!! http://openstudy.com/study#/updates/543de42fe4b0b3c6e146b5e8

  4. anonymous
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    just flip it to the other side y=3x+3 becomes y-3/3=x and y=x-1 becomes y+1=x

  5. anonymous
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    thanksss

  6. texaschic101
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    y = 3x + 3......so now we substitute 3x + 3 in for y in the other equation y = x - 1 3x + 3 = x - 1 --- subtract x from both sides 3x - x + 3 = x - x - 1 -- combine like terms 2x + 3 = -1 --- subtract 3 from both sides 2x + 3 - 3 = -1 - 3 -- combine like terms 2x = -4 -- divide both sides by 2 2/2x = -4/2 x = -2 now we sub in -2 for x in either of the original equations to find y y = 3x + 3 y = 3(-2) + 3 y = -6 + 3 y = -3 now we check.. y = x - 1 -3 = -2 -1 -3 = -3 (correct) so your solution is : (-2,-3)

  7. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...

23

  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.